2002
DOI: 10.1007/s11894-002-0053-8
|View full text |Cite
|
Sign up to set email alerts
|

Sphincter of oddi (pancreatic) hypertension and recurrent pancreatitis

Abstract: Major papilla pancreatic sphincter dysfunction, a variant of sphincter of Oddi dysfunction, causes pancreatitis and pancreatic-type pain. The gold standard for diagnosis is sphincter of Oddi manometry, most commonly performed at endoscopic retrograde cholangiopancreatography (ERCP). Noninvasive testing, such as secretin-stimulated transabdominal or endoscopic ultrasound assessment of pancreatic duct diameter, is less reliable and has relatively low sensitivity. Two thirds of patients with biliary sphincter of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Evidence that SOD may be a cause of IARP is supported by the resolution of pancreatitis after sphincterotomy, with up to 80% improvement in patients with IARP after biliary sphincterotomy [79] . Tarnasky et al [80] showed that biliary sphincterotomy reduced pancreatic basal pressure to within the normal range in 30% of patients immediately after the procedure and 20% after longer term follow up, presumably by ablation of the common channel sphincter, and hence a reduction in the length of the residual pancreatic portion.…”
Section: Pancreatic Type Sodmentioning
confidence: 98%
“…Evidence that SOD may be a cause of IARP is supported by the resolution of pancreatitis after sphincterotomy, with up to 80% improvement in patients with IARP after biliary sphincterotomy [79] . Tarnasky et al [80] showed that biliary sphincterotomy reduced pancreatic basal pressure to within the normal range in 30% of patients immediately after the procedure and 20% after longer term follow up, presumably by ablation of the common channel sphincter, and hence a reduction in the length of the residual pancreatic portion.…”
Section: Pancreatic Type Sodmentioning
confidence: 98%
“…In elderly high-risk patients with gallstone-induced pancreatitis, EST removal of stones from the common bile duct may be sufficient [47]. Whether placement of a pancreatic duct stent concomitantly with EST, which has been reported to lower post-ERCP pancreatitis rates [48,49], is beneficial for patients who undergo EST for biliary pancreatitis is doubtful and needs further evaluation. An algorithm for the treatment of acute gallstone pancreatitis is presented in Figure 2.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…However, manipulation of the papilla (manometry, ERCP, or biliary sphincterotomy) in patients with a hypertensive pancreatic sphincter is associated with an unacceptably high rate of pancreatitis of 20% to 26% [1,55••]. Also, the clinical approach of opening only the biliary sphincter is still associated with a high risk of pancreatitis [1]. However, if biliary sphincterotomy is combined with pancreatic sphincterotomy, the pancreatitis rate drops to about half, and if the drainage of the pancreatic duct is secured by a pancreatic stent, the risk of pancreatitis is reduced from 26% to 6% [55••,56,57].…”
Section: Biliary or Pancreatic Sod As A Clinical Entitymentioning
confidence: 99%
“…However, if biliary sphincterotomy is combined with pancreatic sphincterotomy, the pancreatitis rate drops to about half, and if the drainage of the pancreatic duct is secured by a pancreatic stent, the risk of pancreatitis is reduced from 26% to 6% [55••,56,57]. Thus, it is now generally accepted practice with a hypertensive pancreatic sphincter to place a protective stent or perform a combined sphincterotomy in the initial session [1].…”
Section: Biliary or Pancreatic Sod As A Clinical Entitymentioning
confidence: 99%
See 1 more Smart Citation